2017
DOI: 10.1177/1077800417692362
|View full text |Cite
|
Sign up to set email alerts
|

A Spiritual Question

Abstract: The author explores spirituality and counseling through research poetry created from in-depth interviews with nine counselor educators. The purpose of the narrative study was to explore the religious and spiritual lived experiences of counselor educators and to recognize the impact these experiences may have when counselor educators teach and supervise counseling students. Because spiritual and religious values are an integral element of humanity and development, continual analysis and increased competency for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…This finding is in line with a study by Rose et al (2001) which found that 18% of clients were reluctant to discuss religion and spirituality during therapy sessions with counselors and prefer to discuss it with people who are highly knowledgeable about religion such as scholars or religious leaders, not with counselors. This finding directly shows that counselors need to study their own religion and other religions in preparation for clients of diverse ethnic, racial and ancestral backgrounds before they can apply the religious element in counseling, in order to build the client's trust that they are qualified to discuss religious matters (Damari et al, 2018;Matise et al 2018;Johns, 2017). Mastering religious knowledge is important to enhance the counselor's competency because many clients will have confidence in a counselor who is staunchly religious .…”
Section: 66mentioning
confidence: 99%
“…This finding is in line with a study by Rose et al (2001) which found that 18% of clients were reluctant to discuss religion and spirituality during therapy sessions with counselors and prefer to discuss it with people who are highly knowledgeable about religion such as scholars or religious leaders, not with counselors. This finding directly shows that counselors need to study their own religion and other religions in preparation for clients of diverse ethnic, racial and ancestral backgrounds before they can apply the religious element in counseling, in order to build the client's trust that they are qualified to discuss religious matters (Damari et al, 2018;Matise et al 2018;Johns, 2017). Mastering religious knowledge is important to enhance the counselor's competency because many clients will have confidence in a counselor who is staunchly religious .…”
Section: 66mentioning
confidence: 99%